Adaptive transmission scheme of generalized multi-carrier system based on orthogonal transformation - Pan TIAN; Ming-qi LI; Yun RUI; Min ZHENG; Zhi-yong BU (Tongxin xuebao)
A joint adaptive hybrid single-carrier transmission scheme of orthogonal transformation mode and modulation and coding scheme(MCS)was proposed for orthogonal transformation generalized multi-carrier system(OT-GMC).The scheme achieved the maximal spectrum efficiency by adaptive switching the orthogonal transformation mode and MCS according to effective SINR.When identical transformation was used,the data of each sub-band could be transmitted adaptively and independently.As a result,the spectrum efficiency could be improved.When DFT was used,the signal had lower PAPR and it improved the efficiency of power amplifier.Essentially,this transmission scheme obtains the most optimum compromise performance of spectrum efficiency and PAPR in single-carrier hybrid transmission system.The simulation results show that the presented scheme is better than the single transmission scheme in the aspect of throughput performance.